2012
DOI: 10.1371/journal.pone.0047854
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in White Matter Microstructure in Neurofibromatosis-1

Abstract: Neurofibromatosis (NF1) represents the most common single gene cause of learning disabilities. NF1 patients have impairments in frontal lobe based cognitive functions such as attention, working memory, and inhibition. Due to its well–characterized genetic etiology, investigations of NF1 may shed light on neural mechanisms underlying such difficulties in the general population or other patient groups. Prior neuroimaging findings indicate global brain volume increases, consistent with neural over-proliferation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 62 publications
7
82
4
Order By: Relevance
“…In the healthy brain, voluntary action control engages a frontal cortical-basal ganglia-thalamo-cortical circuit involving frontal cortex projections to the globus pallidus pars interna/externa, via the striatum or the subthalamic nucleus, and then back to the cortex (via the thalamus) (Aron, 2011; Jahfari et al, 2011). Children and adolescents with NF1 present abnormally large striatal and thalamic structures (Violante, Ribeiro, Silva, et al, 2013) as well as white matter microstructural alterations involving particularly the anterior thalamic radiations which connect the thalamus with the frontal lobes, and the cingulate bundle that contains all connections to the cingulate gyrus (Karlsgodt et al, 2012). Abnormal subcortical structure and impaired subcortical–prefrontal connectivity might lead to an abnormal reliance on prefrontal areas for appropriate inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the healthy brain, voluntary action control engages a frontal cortical-basal ganglia-thalamo-cortical circuit involving frontal cortex projections to the globus pallidus pars interna/externa, via the striatum or the subthalamic nucleus, and then back to the cortex (via the thalamus) (Aron, 2011; Jahfari et al, 2011). Children and adolescents with NF1 present abnormally large striatal and thalamic structures (Violante, Ribeiro, Silva, et al, 2013) as well as white matter microstructural alterations involving particularly the anterior thalamic radiations which connect the thalamus with the frontal lobes, and the cingulate bundle that contains all connections to the cingulate gyrus (Karlsgodt et al, 2012). Abnormal subcortical structure and impaired subcortical–prefrontal connectivity might lead to an abnormal reliance on prefrontal areas for appropriate inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with NF1 present increased white matter volume, particularly within the frontal lobe and the corpus callosum, as well as increased grey matter volume, particularly in the thalamus and right caudate nucleus (Duarte et al, 2014; Payne et al, 2010; Violante, Ribeiro, Silva, & Castelo-Branco, 2013). Reduced integrity of white matter microstructure is also found in NF1, suggesting a reduction in effective structural connectivity (Karlsgodt et al, 2012). Functional magnetic resonance imaging (fMRI) studies have suggested functional deficits in several brain regions including deficient visually evoked activation of occipital, temporal and parietal brain regions (Clements-Stephens, Rimrodt, Gaur, & Cutting, 2008; Violante et al, 2012) and abnormal engagement of the frontal lobe (Billingsley et al, 2004; Clements-Stephens et al, 2008; Shilyansky et al, 2010; Violante et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, however, it was shown that NF1 regulates glial cell proliferation and tumor growth in an AKT/mTORC1 dependent but TSC/RHEB independent manner [119] (Figure 1). Although only less than 10% of NF1 patients report seizures [120,121,122], several brain pathological features were frequently described in patients, such as macrocephaly [123,124] and reduced myelination [125,126], as well as in mouse models of the disorder, including larger brains [127], structural malformations [128,129,130], abnormal cerebellar neuronal migration [131,132], increased proliferation and protein synthesis in astrocytes [118,119,133], decreased neurite length [134,135], reduced dendritic spine density [136,137] and impaired LTP [138,139] (Table 1). Among those phenotypic alterations, it has been shown that rapamycin inhibited proliferation and protein synthesis in astrocytes [118,119] (Table 1), indicating that mTORC1 overactivation regulates astrocyte function in NF1 and is probably linked to glioma formation, such that pharmacological inhibition of mTORC1 suppresses tumor growth both in NF1 patients [140,141] and in mouse models [142,143].…”
Section: Mtorc1 Signaling Pathway In Monogenic Autism Spectrum Dismentioning
confidence: 99%
“…Radial diffusion is disproportionately increased; this suggests that looser packing of axons, with or without myelination changes, is a potential alteration contributing to increased cortical white matter in NF-1 [13]. Abnormalities of apoptosis (leading to redundancy of fibers connecting the cerebral hemispheres) have also been postulated as an explanation of the increased white matter volume [12].…”
Section: Neurofibromatosis Typementioning
confidence: 99%